Digital Wounds, Lived Realities: A Synthesis of Evidence on Online Hate and its Impact on Gender and Sexual Minorities in South Africa - Adekola, Ayobami Precious (Journal of Ecohumanism, 2025)
South Africa, despite progressive legislation, continues to grapple with high rates of hate speech and violence against gender and sexual minorities (GSM). Online platforms have become a breeding ground for hate speech, potentially impacting the mental health and social inclusion of GSM individuals. This study employed a qualitative research design, integrating a systematic literature search guided by the PRISMA framework with a thematic analysis of secondary data between 2014–2024 to understand the impact of online hate speech on the mental health and social inclusion of GSM individuals in South Africa. Guided by multi-theoretical frameworks of minority stress theory, cyberpsychology and social identity theory, this study used thematic analysis of peer-reviewed articles focusing on "online hate speech," "GSM," "mental health," "social inclusion," and "South Africa." from databases such as Google Scholar, Scopus, Sabinet, Web of Science, and AJOL and the Directory of Open Access Journals (DOAJ). This study finally included nine papers from the initial 137 articles and documents identified during the search process. This study highlighted the prevalence of online hate speech against South Africa’s LGBTQ+ community, linking it to worsening mental health, social exclusion, and healthcare barriers. It emphasised gaps in legal protections, education, and advocacy. Urgent policy interventions are needed to combat hate speech and support GSM.